[Faculty social breakfast] (1960)
From left to right: Donald S.Nelson, Harold O. Wilson, J. Philip Bromley, Mrs. Harold O. Wilson, Mrs. Robert "Peg" Mott. The breakfast attendees pose while drinking morning coffee.